2021
DOI: 10.3389/fendo.2021.769316
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the BMP Pathway in Prostate Cancer Induced Bone Disease

Abstract: From the 33,000 men in the U.S. who die from prostate cancer each year, the majority of these patients exhibit metastatic disease with bone being the most common site of metastasis. Prostate cancer bone metastases are commonly blastic, exhibiting new growth of unhealthy sclerotic bone, which can cause painful skeletal related events. Patient’s current care entails androgen deprivation therapy, anti-resorptive agents, radiation, and chemotherapy to help control the spread of the cancer but little intervention i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…These include bone morphogenic proteins (BMPs), osteopontin, and the Wnt/β catenin pathway, each of which stimulates downstream Runt‐domain transcription factor signaling and aberrant osteoblast activation. ( 27 , 28 ) Overactive bone formation enhances tumor growth and further compromises the bone marrow compartment. Preclinical models have demonstrated that inhibition of BMP signaling in particular can limit the osteoblastic response and, to some extent, indirectly suppress tumor growth ( 27 ) ; however, to date these approaches have not translated to the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…These include bone morphogenic proteins (BMPs), osteopontin, and the Wnt/β catenin pathway, each of which stimulates downstream Runt‐domain transcription factor signaling and aberrant osteoblast activation. ( 27 , 28 ) Overactive bone formation enhances tumor growth and further compromises the bone marrow compartment. Preclinical models have demonstrated that inhibition of BMP signaling in particular can limit the osteoblastic response and, to some extent, indirectly suppress tumor growth ( 27 ) ; however, to date these approaches have not translated to the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…BMPs have recently been shown to have expanded roles in osteoclasts and bone resorption which can be instrumental in the heightened lytic vicious cycle of tumor induced bone disease 49,50 . BMP inhibition of lytic‐like lesions may be more preferential than blastic‐like lesions if those lesions are driven by BMP‐directed osteoclastogenesis as compared to TGFβ‐driven sclerosis 51 . It has also been demonstrated in multiple myeloma that BMP inhibition of osteolytic lesions improved bone quality through combined lineages of bone matrix producing cells 52 .…”
Section: Discussionmentioning
confidence: 99%
“… 49 , 50 BMP inhibition of lytic‐like lesions may be more preferential than blastic‐like lesions if those lesions are driven by BMP‐directed osteoclastogenesis as compared to TGFβ‐driven sclerosis. 51 It has also been demonstrated in multiple myeloma that BMP inhibition of osteolytic lesions improved bone quality through combined lineages of bone matrix producing cells. 52 Genetic and pharmacologic loss of function studies for BMPR1a have surprisingly resulted in improvement in bone formation as opposed to expected loss in BMP directed osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In myeloma bone disease, inhibition of BMP signaling prevented bone loss by reducing osteoclastogenesis and promoted osteoblast differentiation by reducing the concentration of sclerostin the bone marrow [123]. Pharmacologic inhibition of BMP signaling by small molecule antagonist DMH1 in prostate cancer models of bone metastasis restricted cancer cell colonization to bone in immunodeficient mice; however, in mice with intact immune system, DHM1 had no effect on tumor growth and bone health [124]. Interestingly, numerous studies identified a dual role of BMPs in cancer development with BMPs acting both as tumor promoters or suppressors [125].…”
Section: Growth Factors Mediating Bone Defectsmentioning
confidence: 99%